The impact of EI generosity on post-claim employment - Lluis, Stephanie (My University, 2022)
The researchers analyze two Employment Insurance (EI) initiatives that extended the benefit duration and the allowable earnings criterion for claimants working while on claim. They study the impact of the initiatives on transitions into full-time employment, part-time employment and on job search. They review evidence from the multiple pilots of the Working While on Claim (WWC) program whereby EI claimants can keep a portion of their benefits while working a part-time job, implemented over 2005-2018, to determine if the provisions facilitate a return to permanent and full-time work. They also survey the outcomes of similar provisions in other countries.
Keywords: Government; Income, pensions, spending & wealth; Labour